Relationship between Major Stock Market Indices and Economic Growth in Selected Market Economies. A Study of Emerging Economies - Achugbu , Austine A.; Nduka, Joseph A. (African Journal of Education,Science and Technology (AJEST), 2017)
The study empirically probed the relationship between major stock market indices and economic growth in selected market economies of emerging markets. The specific objective of this study is to validate if the stage of economic development in emerging economies has any impact on the stock market size and economic growth and whether the stock market liquidity has any effect on economic growth in emerging economies. Variables used in the analysis were subjected to two types of unit root text; Im, Persaran and shin test and Levin, lin and chu test to determine whether they are stationary series or non-stationary series. Two panel regression analysis were carried out (fixed and Random- effect) and Hausman test was used to decide which of the result to abide by. It was observed that in emerging economies, stock market size measured in terms of Market Capitalization Ratio (MCR) was found to have significant positive effect on economic growth. While interest rate exerted positive impact on economic growth in other economics, it was the reverse in emerging economies. Furthermore, stock market liquidity measured in terms of Value Traded Ration (VTR) and Turnover Ratio (TOR) were found to have mixed impact on economic growth of emerging economies. It was only in emerging economies that the interest rates channel had significant impact on the relationship between stock liquidity and economic growth. It is therefore imperative for the government to factor in the stage of economic development when formulating polities that are meant to stimulate economic growth through stock market size and stock market liquidity